Implantable Soft Neural Electrodes of Liquid Metals for Deep Brain Stimulation - Kwon, Yong Won; Kim, Enji; Koh, Chin Su; Park, Young-Geun; Hong, Yeon-Mi; Lee, Sanghoon; Lee, Jakyoung; Kim, Tae Jun; Mun, Wonki; Min, Seung Hyun; Kim, Sumin; Lim, Jung Ah; et al. (American Chemical Society, 2025)
Stimulating large volumes of neural networks using macroelectrodes can modulate disorder-associated brain circuits effectively. However, conventional solid-metal electrodes often cause unwanted brain damage due to their high mechanical stiffness. In contrast, low-modulus liquid metals provide tissue-like stiffness while maintaining macroscale electrode dimensions. Here, we present implantable soft macroelectrodes made from biocompatible liquid metals for brain stimulation. These probes can be easily fabricated by simply filling polymeric tubes with a liquid metal, offering a straightforward method for creating brain stimulation devices. They can be customized in various lengths and diameters and also serve as recording microelectrodes. The electrode tips are enhanced with platinum nanoclusters, resulting in low impedance and effective charge injection while preventing liquid metal leakage into brain tissue. In vivo experiments in neuropathic pain rat models demonstrate the stability and effectiveness of these probes for simultaneous neural stimulation and recording, demonstrating their potential for pain alleviation and behavioral control.